Pengaruh Modal Usaha, Literasi Keuangan, dan Manajemen Kas Terhadap Keberlanjutan Usaha TKM Pemula Di Kota Bekasi - Jordan, Steven; Yahya, Adibah; Nurjanah, Rina (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to assess the impact of venture capital, financial literacy, and cash management on business sustainability business of beginer Self-Employed Workers in Bekasi City. This research is motivated by the importance of beginer Self-Employed Workers in the Indonesian economy and the challenges they face in maintaining business sustainability. The method used is quantitative analysis using the Partial Least Square (PLS) approach in Structural Equation Modeling (SEM), involving 100 respondents who are recipients of the beginer Self-Employed Workers assistance program in Bekasi City. The research findings show that business capital has a negative effect on business continuity. On the other hand, financial literacy and cash management have a positive and significant influence on business sustainability. Effective cash management helps beginer Self-Employed Workers to maintain liquidity and promote business growth, while good financial literacy allows beginer Self-Employed Workers to make more informed decisions. This research provides valuable information for the managers of the beginer Self-Employed Workers program to help the sustainability of the business in the future.